2015
DOI: 10.1590/s1806-37132015000004518
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in rheumatoid arthritis: evaluation by radiography and spirometry

Abstract: Objective: To determine whether simple diagnostic methods can yield relevant disease information in patients with rheumatoid arthritis (RA). Methods: Patients with RA were randomly selected for inclusion in a cross-sectional study involving clinical evaluation of pulmonary function, including pulse oximetry (determination of SpO2, at rest), chest X-ray, and spirometry. Results: A total of 246 RA patients underwent complete assessments. Half of the patients in our sample reported a history of smoking. Spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(75 reference statements)
4
7
1
1
Order By: Relevance
“…In the present study, we found significantly lowered FVC, FEV 1 and PEFR in RA patients at baseline (before MTX therapy) than those of control group. Similar findings were observed by several investigators 5,8,25,30 . The cause of our finding might be due to movement limitation of chest cage,because of synovial joint affection (specially, costovertebral and costochondral) [33][34] or respiratory muscle weakness 13, 33-35[43] or inflammatory change in the bronchi 13,29,[33][34] in RA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found significantly lowered FVC, FEV 1 and PEFR in RA patients at baseline (before MTX therapy) than those of control group. Similar findings were observed by several investigators 5,8,25,30 . The cause of our finding might be due to movement limitation of chest cage,because of synovial joint affection (specially, costovertebral and costochondral) [33][34] or respiratory muscle weakness 13, 33-35[43] or inflammatory change in the bronchi 13,29,[33][34] in RA.…”
Section: Discussionsupporting
confidence: 92%
“…Significantly lower mean percentages of predicted value of FVC in RA patients without [5][6][24][25] and after low dose MTX therapy have been reported [26][27] . On the other hand, non-significant decrease in FVC value after MTX treatment in patients with RA has also been published [28][29] .…”
Section: Introductionmentioning
confidence: 86%
“…Alexandre Melo Kawassaki et al 20 observed the chest X-rays were normal (55.3%) of the patients; hyperinflation was present in (24.8%); the interstitial pattern was observed in (14.6%); volume loss was observed in (2.4%) and miscellaneous abnormalities were observed in the remaining (2.8%).…”
Section: Discussionmentioning
confidence: 97%
“…They reported that smoking or methotrexate may be a risk factor for pulmonary disease. Moreover, Kawassaki et al 31 investigated pulmonary disease in patients with RA and found that lung involvement was related to smoking. In our study, lung involvement was determined in 40 patients out of 165 (24.2%).…”
Section: Discussionmentioning
confidence: 99%